Efficiency of Rice Processing Among Women Processors in Southern Taraba, Taraba State, Nigeria - N. K. Mikailu; F. B. Filli; U. H. Ukpe (Darul Yasin Al Sys, 2026)
Rice processing plays an important role in rural livelihoods and local food systems in Nigeria; however, evidence on the economic efficiency of women processors remains essential for informing productivity-enhancing interventions. This study analyzed the efficiency of rice processing among women processors in Southern Taraba, Taraba State, Nigeria. A multi-stage sampling technique was used to select 70 respondents from Wukari and Donga Local Government Areas. Primary data were collected through structured questionnaires and analyzed using descriptive statistics, gross margin analysis, and net income estimation. The results showed that 89% of the processors were aged 50 years or below, with a mean age of 38.6 years, indicating a relatively young and active workforce. Most respondents had formal education (90%), 63% were married, and the average household size was five persons. Profitability analysis demonstrated that rice processing was a viable enterprise, with a total revenue of ₦711,064.40 and a total cost of ₦471,638.87 per processing day, resulting in a gross margin of ₦240,751.33 and a net income of ₦239,425.53. The return per naira invested was 0.51, implying that processors realized a gain of 51 kobo for every naira invested. Paddy rice constituted the largest cost component, accounting for 90.37% of variable costs. The study concludes that rice processing among women in the study area is profitable, although its efficiency is constrained by inadequate capital, limited access to modern equipment, and insufficient technical training. These findings highlight the need for improved access to modern milling technology, credit facilities, and regular capacity-building programs to enhance processing efficiency and support broader food security goals in Nigeria.